The GhMAX2 gene regulates plant growth and fiber development in cotton - Peng HE; Hui-zhi ZHANG; Li ZHANG; Bin JIANG; Guang-hui XIAO; Jia-ning YU (Journal of Integrative Agriculture, 2022)
Strigolactones (SLs) are a new type of plant endogenous hormones that have been found to regulate plant growth and architecture. At present, some genes related to the biosynthesis and signaling pathway of SLs have been isolated in plants such as Arabidopsis thaliana, Pisum sativum and Oryza sativa. However, the signaling pathway and specific mechanism of SLs in cotton remain unclear. In this study, we identified the SLs signaling gene GhMAX2 and demonstrated its function in plant growth and architecture in Gossypium hirsutum. Bioinformatics analysis showed that GhMAX2 mainly consists of an α-helix and a random coil and includes a large number of leucine-rich repeats. GhMAX2 was highly expressed in root, stem, flower, and fibers at 20 days post-anthesis (DPA). GhMAX2 promoter-driven β-glucuronidase expression was present exclusively in the root, main inflorescence, flower, and silique. Subcellular localization showed that GhMAX2 is targeted to the nucleus. Heterologously expressed GhMAX2 can rescue the phenotype of Arabidopsis max2-1 mutant, indicating that the function of MAX2 is highly conserved between G. hirsutum and A. thaliana species. In addition, the knockdown expression of GhMAX2 in cotton resulted in significantly reduced plant height, slow growth, short internodes, and reduced ﬁber length. These findings indicate that GhMAX2 probably contributes to plant growth, architecture and fiber elongation in cotton. The study reveals insights into the roles of GhMAX2-mediated SL/KAR signaling in cotton and provides a valuable foundation for the cultivation of cotton plants in the future.